Making sense of agile project management : balancing control and agility - Cobb, Charles G., 1945- (Hoboken, N.J. : Wiley, 2011)
'The book is intended to provide a much deeper understanding of agile principles, methodologies, and practices to enable project managers to develop a more agile approach and understand how to blend and tailor agile and traditional principles, methodologies, and practices to create an appropriate balance of control and agility to fit a business environment as well as the risks and complexities of any individual project. The book will also provide business managers and leaders an understanding of how to fit agile methodologies into an overall business strategy that provides the right balance of control and agility for their business'--
Includes bibliographical references and index.
Keywords: Software engineering; Computer software -- Development -- Management; Agile software development